Predictors of Weight-Related Quality of Life in Adolescents Who Are Overweight or Obese. Issue 2 (February 2018) - Ievers-Landis, Carolyn E.; Olayinka, Oluwatomisin; Burant, Christopher; Moore, Shirley
ABSTRACT: Objective: Weight-related quality of life (WRQOL) is a type of health-related QOL that may serve as a patient-reported outcome of the potential burden of overweight. The present study uses structural equation modeling path analysis methods to examine body mass index (BMI) and other potential predictors of WRQOL components among adolescents who were overweight/obese from predominantly low-income, urban households. Methods: Baseline data were obtained from 360 participants (10–13 year olds; 57.8% female; 76.7% black; average BMI of 27.12) and their parents/legal guardians from a randomized, controlled, treatment trial. Youth completed measures of WRQOL, depressive symptoms, and family/friend social support for healthy eating. Parents completed measures of demographics and child social problems. Results: The initial model included BMI, gender, parent education, family/friend social support for healthy eating, child social problems, body esteem and social life WRQOL, and depressive symptoms. The final model fit the data well (χ 2 = 27.738; df = 16; p = .034). Higher BMI was indirectly related to lower social life and body esteem WRQOL through greater social problems. Physical comfort and family relations WRQOL were unrelated to BMI and were not included. Lower social life and body esteem related to more depressive symptoms. Family/friend discouragement for healthy eating was associated with lower body esteem; also, family discouragement was related to lower social life. Conclusion: Body mass index may not directly relate to WRQOL but may be associated through other factors, including child social problems. Interventions should screen for and treat mood and social problems and address family/friend support for healthy eating.